Mesleksel yaralanma ve ölümlerde bölgesel eşitsizlikler/Regional inequalities in occupational injuries and deaths - Alpaslan Türkkan (Turkish Society of Public Health Specialists, 2013)
Özet Amaç: Türkiye'de mesleksel hastalıklar ile iş kazaları nedeniyle oluşan yaralanma ve ölümlerde bölgesel eşitsizlikleri değerlendirmektir. Yöntem: Ekolojik tipteki çalışma 2000-2011 yılları arası 12 yıllık döneme ait mesleksel güvenlik ve sağlık verisinin retrospektif olarak incelenmesiyle yürütülmüştür. Veri kaynağı Sosyal Güvenlik Kurumu (SGK) ve Sosyal Sigortalar Kurumu (SSK) istatistik yıllıklarıdır. Zorunlu sigortalıların yaralanma ve ölüm verisi iller bazında kaydedilmiştir. Veri İstatistiki Bölge Birimleri Sınıflaması'na (İBBS) uygun şekilde birleştirilerek bölgesel veri haline dönüştürülmüştür. Yaralanma insidans hızı, mortalite ve fatalite hızları bu veriden hesaplanmıştır. Bölgesel eşitsizlikleri göstermek için risk oranı, risk farkı, topluma atfedilen risk (PAR) ve yüzdesi (PAR%) hesaplanmıştır. Bulgular: Türkiye'de 2000-2011 yılları arasında iş nedeniyle yılda ortalama 74.215 kişi yaralanmış ve 1.092 kişi ölmüştür. Türkiye'de 2000-2011 yılları arasında mesleksel yaralanma insidans hızı %58, mortalite hızı %27,3 azalırken fatalite hızı %73,4 artmıştır. Mutlak eşitsizlik göstergesi olan fatalite hızı risk farkı 2000 yılındaki 50,9'dan 2011 yılında 128,0'a yükselmiştir. Bölgesel eşitsizlikler olmasaydı 2000-2011 arasındaki 13.099 iş nedenli ölüm sayısı 6.511'e düşecekti. Sonuç: İş kazaları ve meslek hastalıkları nedeniyle yaralanma ve ölümlerde bölgelerarası eşitsizlikler belirgindir. Türkiye'de mesleksel hastalık ve iş kazası kayıtları yetersiz olup tüm olgular bildirilmemektedir. Bu nedenle mesleksel güvenlik ve sağlık durumu değerlendirilirken fatalite hızı da göz önüne alınmalıdır. Anahtar Kelimeler: Mesleksel yaralanma, meslek hastalığı, mortalite, fatalite Abstract Objective: To evaluate the injuries and the deaths due to occupational diseases and occupational accidents in Turkey with respect to inter-regional inequalities. Methods: This ecological type of study was conducted between the years of 2000-2011 by examining the occupational safety and the health data for the 12 years retrospectively. The data sources were the statistical year books from Social Security Institution (SSI) and Social Insurance Institution (SII). The data for the injuries and deaths of the compulsory insured individuals were recorded on a city basis. The set of data created by cities have been put into regional data categories with respect to the Nomenclature of Territorial Units For Statistics (IBBS). Occupational injury incidence, mortality and fatality rates have been calculated based on the present data. To show the regional inequalities risk ratios, risk differences, absolute population attributable risks (PAR) and the ratios (PAR%) have been calculated. Results: 74,215 people were injured and 1,092 died due to occupational accidents between 2000-2011. During the 12 year period the injury incidence rate decreased by 58%, the mortality rate by 27.3% but the fatality rate increased by 73.4%. The risk difference of the fatality rate which is an indicator of absolute inequality has risen to 128.0 in 2011 from the 50.9 rate in 2000. If there were no regional inequalities the number of death between 2000-2011 would go down to 6,511 from 13,099. Conclusions: Regional inequalities are present for injuries and deaths due to occupational accidents & diseases. There is a dearth of records on occupational diseases and accidents in Turkey and very few of the incidents are being reported. Therefore, the fatality rate should be taken into consideration, when the occupational safety and health status are being examined. Key Words: Occupational injury, occupational diseases, mortality, fatality